Bibliometric Analysis: Mental Health Problems in a Decade - Maghfiroh, Nasruliyah Hikmatul; Sukmawati, Bhennita (Westscience Press, 2024)
This paper provides a thorough bibliometric analysis of research on mental health published in the last ten years (2014–2024). Mental health issues affect people all around the world, affecting families, communities, and healthcare systems. To spot trends, knowledge gaps, and areas in need of more research, it's critical to comprehend the scientific landscape of mental health research. Using information from 3,588 Scopus databases that were published in the last ten years, this study looked at the journal landscape, citation trends, and publishing trends in mental health research. The analysis draws attention to the growing number of research papers, the significance and power of scholarly work, and the importance of major media outlets on the subject. The findings collected from this study can help policymakers, practitioners, and researchers promote evidence-based interventions, fill research gaps, and advance knowledge to enhance mental health outcomes worldwide.